Pendidikan Karakter dan Krisis Moral Generasi Z - Miranda Cahyani; Indah Nur Lathifiyah; Yahya Ashari (Indo Publishing, 2026)
This study aims to analyze the role of character education in addressing the moral crisis among Generation Z in the digital age. The method used is a literature review examining various relevant scientific sources related to character education and the moral development of the younger generation. The results of the study indicate that Generation Z exhibits a tendency toward moral degradation, characterized by declining communication ethics, low social empathy, and increasing individualistic behavior due to the dominance of digital media. Character education plays a crucial role in shaping an individual’s personality through the instillation of moral values such as honesty, responsibility, and social concern. However, its implementation in practice remains suboptimal as it tends to be theoretical and has not yet been integrated into the real-life experiences of students. Therefore, there is a need to strengthen character education that is adaptive to the times, particularly by integrating moral values within a digital context. Thus, character education is expected to serve as a solution to address the moral crisis among Generation Z and to shape individuals who are not only intellectually intelligent but also of noble character.